VARIATION OF POTATO STARCH AND BAGASSE CELLULOSE ON THE PHYSICAL AND MECHANICAL PROPERTIES OF BIOPLASTICS - Sulkha, Amalia; ., Masthura; Jumiati, Ety (Universitas Negeri Medan, 2024)
Bioplastics are ordinary plastics that can be used, but can be decomposed by microorganisms, so they are environmentally friendly. The aim of this research is to determine the characteristics of potato starch and bagasse cellulose bioplastics and to determine variations that produce compositional characteristics with the best quality for making bioplastics using potato starch and bagasse cellulose as basic ingredients. Samples A (75% : 25%), B (50% : 50%), and C (25% : 75%) have different compositions of potato starch and bagasse cellulose. To make bioplastic, magenectic is used for one hour at a speed of 500 rpm and a temperature of 80 °C. The size of the mold is 20 x 20 x 1 cm3, and drying is carried out in an oven at 50°C for 12 hours. This research has several tests, namely physical tests including water absorption tests refers to ASTM D570-98, and the biodegradable test follows SNI 7188.7:2016. Test The mechanism includes the tensile strength test of the SNI 06-1315-2006 testing standard.